Gender Discrimination and Difficulties faced by Women in Workplace in South West Nigeria - Hussaini, Olusola Adenike; Abanikannda, Mutahir Olufemi; Surakat, Olabanji Ahmed (NIU Journal of Social Sciences, 2025)
This study explores gender discrimination and difficulties faced by women in the workplace in South-West Nigeria, motivated by the pressing issue of women's limited participation and progress in the labor market. The research aimed to investigate the challenges women face, the role of company culture in perpetuating discrimination, and the impact of technological revolution on promoting equal opportunities. A descriptive research survey design was employed, with a sample of 1,800 participants from six polytechnics. The results showed that women face significant difficulties, including micro-aggressions, subtle discrimination, and unequal treatment. Company culture was found to perpetuate discrimination, with high agreement rates on issues like discouraging challenges to discriminatory practices and perpetuating gender stereotypes. However, the technological revolution was found to promote equal opportunities, fairness, and inclusivity. The study concludes that stakeholders should invest in digital literacy programs and promote inclusive tech policies to bridge the gender gap in the workplace. This study's findings have implications for policymakers, organizations, and individuals seeking to promote gender equality and women's empowerment in the workplace. The study's innovative approach highlights the potential of technology to drive positive change in the workplace. Keywords: Workplace inequality, female empowerment, organizational culture, technological inclusion.